2018
DOI: 10.1038/s41467-018-03257-1
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent manganese based anodes and co-solvent electrolyte for stable low-cost high-rate sodium-ion batteries

Abstract: The demand of sustainable power supply requires high-performance cost-effective energy storage technologies. Here we report a high-rate long-life low-cost sodium-ion battery full-cell system by innovating both the anode and the electrolyte. The redox couple of manganese(I/II) in Prussian blue analogs enables a high-rate and stable anode. Soft X-ray absorption spectroscopy and resonant inelastic X-ray scattering provide direct evidence suggesting the existence of monovalent manganese in the charged anode. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 36 publications
3
76
0
Order By: Relevance
“…[ 4–8 ] Among these, the sodium‐ion batteries (SIBs) have received growing research attention, on account of the inexhaustible and low‐cost nature of sodium resource, as well as its suitable redox potential and safety. [ 9–12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 4–8 ] Among these, the sodium‐ion batteries (SIBs) have received growing research attention, on account of the inexhaustible and low‐cost nature of sodium resource, as well as its suitable redox potential and safety. [ 9–12 ]…”
Section: Introductionmentioning
confidence: 99%
“…As a result, improved sodium storage performance has been observed in a variety of anode materials, after using ester‐based electrolytes rather than its ether analogue . Cohn et al demonstrated that highly crystalline few‐layered graphene can act as an ultrafast Na‐ion anode in NaPF 6 ‐diglyme system, where a diglyme solvent shell is able to encapsulate a sodium ion as “nonstick” coating to help rapid ion insertion (Figure A,B).…”
Section: Ether‐based Electrolytesmentioning
confidence: 99%
“…75 As a result, improved sodium storage performance has been observed in a variety of anode materials, after using ester-based electrolytes rather than its ether analogue. [76][77][78][79][80][81] Cohn et al 76 demonstrated that highly crystalline few-layered graphene can act as an ultrafast Na-ion anode in NaPF 6diglyme system, where a diglyme solvent shell is able to encapsulate a sodium ion as "nonstick" coating to help rapid ion insertion ( Figure 5A,B). Xu's research group 77 developed a novel strategy of decoupling the merits of ester-and ether-based electrolytes to enable HC anode with superior cycle performance ( Figure 5C).…”
Section: Ether-based Electrolytesmentioning
confidence: 99%
“…(j) Mn L 3 ‐edge sXAS spectra (left) and N K‐edge sXAS spectra (right) at different states of charge. Reprinted with permission from (i)–(j) . Copyright 2018 Springer Nature.…”
Section: Xas Techniques For Prussian Blue Analogues For Sibsmentioning
confidence: 99%